Partial characterization of bacteriocin-like compounds from two strains of Bacillus cereus with biological activity against Paenibacillus larvae, the causal agent of American Foulbrood disease - Alippi Adriana M. (2016)
American Foulbrood (AFB), caused by the spore-forming Gram-positive bacteriumPaenibacillus larvae,is the most severe bacterial disease affecting honeybees worldwide. Two bacterial isolates showing specific inhibitory activity againstP.larvaewere identified asBacillus cereusby 16S rDNA sequencing. Antagonistic compounds were obtained from cell-free supernatants of strains m6c and m387 growing on Trypticase Soy Broth and concentrated by NH4SO4precipitation, ultrafiltration and butanol extraction. Both compounds were characterized as bacteriocin-like inhibitory substances (BLIS). BLISm6c and BLISm387 were stable at 70°C for 30min and active in the pH range from 3 to 7. The antibacterial activity was completely lost at pH values higher than 8 or temperatures >80°C. Both BLIS have a narrow activity range and highly inhibit the growth ofP.larvae. BLISm6c and BLISm387 differ from each other and other BLIS reportedly produced byB.cereuswith regard to their molecular weights, antibacterial activity, minimal inhibitory concentration values and sensitivity to degradative enzymes. The findings of this study suggest that BLISm6c and BLISm387 can potentially be used to control AFB.